The quality of life of labor migrants’ children - G.D. Gorbunova (Medičnì Perspektivi)
In order to define the quality of life of labor migrants’ children, there were researched different aspects of their lives, such as physical functioning (PF), emotional functioning (EF); social functioning (SF) and school functioning (SF). The given research involved 150 children from Republic of Moldova. They were of different age groups (5-7, 8-12, 13-18), of whom 75 children were of the labor migrants and their parents/guardians who remain in the country and 75 children of labor migrants and their parents without labor migration experience. As the instrument for given research there was used the Pediatric Quality of Life Inventory (PedsQL™4.0) questionnaire. In the course of the research there was distinguished Quality of Life (QL) of children on high level, score from 100 to 91, the middle level – from 90 to 81, the low level – from 80 to 71 and the lowest level, less than 70 scores. According to the results of the investigation it was established that the migrants’ children of various age groups, from all the examined aspects had a very low level of QL (less than 70 scores). In all age groups presented by the migrants’ children, the QL in terms of physical functioning, has a considerably lower level of scores (р<0.001) in comparison to the children from the control group. The highest level of QL was observed in the group of children aged 5-7 and the lowest in 13-18 aged group. There was also evidentiated a very low level of QL of the migrants’ children in emotional aspect (from 42.0±25.32 to 43.7±25.94 scores), that considerably differs (р<0.001) from the middle level of QL of the children from the examined group (from 85.0±19.83 to 89.0±20.82 scores). The lowest data of QL in the emotional aspect of the migrants’ children aged 13-18 years old (42.0±25.32), demonstrate a very specific emotionally stressed state of these children. Migrants’ children demonstrate a very low level of QL in terms of social functioning and it certainly differs from the middle level of QL of the children from the examined group. That definitely demonstrates a low ability to social adaptation of children after their parents’ migration. The lowest indicators of the total score of QL were revealed at the age of 13-18, both in groups of migrants’ children (46.8±24.19 scores) and in the examined group of children (82.7±19.57 scores). At the same time the highest indicators of the total score of QL were revealed at the age of 5-7, both in groups of migrants’ children (55.9±30.85 points), and children of the examined group (85.9±23.70 scores). The presented results perform a very convincing fact that labor migrants’ children in comparison to their peers from the families without labor migration experience had considerably low indices by all scales and integral characteristics of quality of life.